Kepercayaan Produk Halal Mempengaruhi Minat Beli Yang Berdampak Pada Keputusan Pembelian - Riyadi, Sugeng; Yuniarso, Yudi Budi; Mansur, Mansur; Sari, Yuli Indah; Bahrudin, Bahrudin (LPPM Institut Pendidikan Nusantara Global, 2025)
This study aims to examine the influence of knowledge about halal products, religiosity, and halal labels on purchasing decisions, with purchase intention as a mediating variable. The research focuses on Muslim consumers from Generation Z and involves 450 respondents. A descriptive quantitative approach was employed, with data analysis processed using Smart PLS. The findings indicate that knowledge of halal products and religiosity have a positive and significant impact on purchase intention, while the halal label has no effect. Purchase intention was found to have a positive and significant impact on purchasing decisions, whereas knowledge of halal products and religiosity do not have a direct influence. Conversely, the halal label has a positive and significant effect on purchasing decisions. Additionally, purchase intention mediates the relationship between knowledge of halal products and religiosity on purchasing decisions but does not mediate the relationship between the halal label and purchasing decisions. These findings provide insights for producers to enhance the appeal of halal products among Muslim Generation Z consumers.